Quantification of regional early stage gas exchange changes using hyperpolarized 129Xe MRI in a rat model of radiation‐induced lung injury. Issue 5 (19th April 2016) - Doganay, Ozkan; Stirrat, Elaine; McKenzie, Charles; Schulte, Rolf F.; Santyr, Giles E.
Abstract : Purpose: To assess the feasibility of hyperpolarized (HP) 129 Xe MRI for detection of early stage radiation‐induced lung injury (RILI) in a rat model involving unilateral irradiation by assessing differences in gas exchange dynamics between irradiated and unirradiated lungs. Methods: The dynamics of gas exchange between alveolar air space and pulmonary tissue (PT), PT and red blood cells (RBCs) was measured using single‐shot spiral iterative decomposition of water and fat with echo asymmetry and least‐squares estimation images of the right and left lungs of two age‐matched cohorts of Sprague Dawley rats. The first cohort ( n = 5) received 18 Gy irradiation to the right lung using a 60 Co source and the second cohort ( n = 5) was not irradiated and served as the healthy control. Both groups were imaged two weeks following irradiation when radiation pneumonitis (RP) was expected to be present. The gas exchange data were fit to a theoretical gas exchange model to extract measurements of pulmonary tissue thickness ( L PT ) and relative blood volume ( V RBC ) from each of the right and left lungs of both cohorts. Following imaging, lung specimens were retrieved and percent tissue area (PTA) was assessed histologically to confirm RP and correlate with MRI measurements. Results: Statistically significant differences in L PT and V RBC were observed between the irradiated and non‐irradiated cohorts. In particular, L PT of the right and left lungs was increased approximately 8.2% and 5.0% respectively in the irradiated cohort. Additionally, V RBC of the right and left lungs was decreased approximately 36.1% and 11.7% respectively for the irradiated cohort compared to the non‐irradiated cohort. PTA measurements in both right and left lungs were increased in the irradiated group compared to the non‐irradiated cohort for both the left ( P < 0.05) and right lungs ( P < 0.01) confirming the presence of RP. PTA measurements also correlated with the MRI measurements for both the non‐irradiated ( r = 0.79, P < 0.01) and irradiated groups ( r = 0.91, P < 0.01). Conclusions: Regional RILI can be detected two weeks post‐irradiation using HP 129 Xe MRI and analysis of gas exchange curves. This approach correlates well with histology and can potentially be used clinically to assess radiation pneumonitis associated with early RILI to improve radiation therapy outcomes.